1985
DOI: 10.1007/bf01732171
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone-treated patients with suppressed TSH test are at risk of thyrotoxicosis

Abstract: Therapeutic use of the potent antiarrhythmic drug amiodarone requires early detection of impending hyperthyroidism, a potentially life-threatening adverse reaction in cardiac patients. Since amiodarone inhibits peripheral conversion of thyroxine (T4) to triiodothyronine (T3), serum T4 and T3 levels become unreliable parameters of thyroid function. In 44 patients treated with amiodarone for a median period of 7.3 months, up to seven TRH-TSH tests were performed. The TSH response to TRH was normal in 23 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Whether such decreased serum levels of TSH or a suppressed response of TSH to TRH test [25] may predict the development of clinically overt AIT remains to be elucidated in a prospective study in a greater number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Whether such decreased serum levels of TSH or a suppressed response of TSH to TRH test [25] may predict the development of clinically overt AIT remains to be elucidated in a prospective study in a greater number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Trip et al (44) observed that the average length of amiodarone treatment before the occurrence of AIT was about 3 yr, with a probability of 0.025 after 18 months and 0.335 after 48 months. There are no parameters allowing predictability of AIT (44), although it has been suggested that the baseline lack of a TSH response to TRH may represent a risk factor for the subsequent occurrence of AIT (70). Mariotti et al (66) reported the occurrence of AIT after 21-47 months of amiodarone therapy.…”
Section: April 2001mentioning
confidence: 99%
“…TSH binding-inhibiting autoanti bodies (TBIAb) were measured by radioreceptor as say using a commercial kit (TBIAb Kit, Byk Mallinckrodt, Milan, Italy). Thyroid stimulating autoanti bodies (TSAb) were assayed by adenylate cyclase stimulation in human thyroid plasma membranes [57]. Urinary iodine excretion was measured by the modified method of Zac and the results were ex pressed as microgram iodine per gram creatinine.…”
Section: Methodsmentioning
confidence: 99%
“…However, either suppressed basal TSH values or absent TSH response to TRH were often found also in euthyroid subjects chronically treated with amiodarone [35]. This finding was interpreted as a prognostic index for the possible evolution toward thy rotoxicosis [57]. Radioiodine Uptake Twenty-four-hour RAIU was available in 43 AIIT patients.…”
Section: Serum Thyroid Hormone Concentrationsmentioning
confidence: 99%